Prevalence of Eimeria Schneider, 1875 in Layer Chicken of Some Poultry Farms of Kathmandu and Lalitpur Districts - Jayswal, Rakesh Prasad; Gupta, Ranjana; Shrestha, Swoyam Prakash (Journal of Natural History Museum, 2015)
In the present study five Eimeria species viz. Eimeria tenella, E. acervulina, E. necatrix, E. maxima and E. brunetti responsible for coccidiosis are reported and its general prevalence was found to be 24 percent. Among the five Eimeria species, prevalence of E. tenella was recorded to be the highest (25%), followed by E. acervulina (15%), E. necatrix (10%). E. maxima (7%) and E. brunetti (3%). Altogether 400 stool samples (dropping) were collected by random sampling methods from four poultry farms. These samples were preserved in preservative solution (2% potassium dichromate solution). Stool samples were examined by thin feacal smear methods. There were altogether 96 cases of coccidiosis of which 25% were caecal, 35% intestinal and 40% mixed. Prevalence of coccidiosis was recorded in all the 12 months and four seasons of the study period. The highest (38%) prevalence rate was found in the month of July and the lowest (5.71%) in the month of October. The difference in monthly prevalence of Eimeria was insignificant (x2 =19.675, P<0.05). Similarly season wise prevalence showed the highest (35%) prevalence rate in the spring season followed by summer (25%), winter (23%) and autumn (12%). Season-wise difference in prevalence of Eimeria was found to be insignificant (x2= 7.815, P> 0.05). The age- wise prevalence was the highest (34.66%) in 61 weeks above chicken, followed by 30% in the 46-60 weeks age group, 22.5% in the 31-45 weeks age group, 17.14% in the 0-15 weeks age group and 15.78% in the 16-30 weeks age group. The difference in age- wise prevalence was found to be insignificant (x2= 9.488,P> 0.05). J. Nat. Hist. Mus. Vol. 28, 2014: 66-72